Dimension formulas for the free nonassociative algebra (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
The free nonassociative algebra contains two subspaces closed under both the commutator and the associator: the Akivis elements and the primitive elements. Every Akivis element is primitive, but there are primitive elements which are not Akivis.